1999
DOI: 10.1523/jneurosci.19-15-06338.1999
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Branch-Specific Export of mRNA Are Regulated by Synapse Formation and Interaction with Specific Postsynaptic Targets

Abstract: Mechanosensory neurons (SNs) of Aplysia form synapses in culture with some targets (L7), but not others (L11), even when a SN is plated with both targets. We examined whether branch-specific net export of mRNA encoding synapse-specific molecules might contribute to branch-specific synapse formation. Single-cell RT-PCR was used to assay levels of mRNA encoding the SN-specific neuropeptide (sensorin A) and other transcripts in cell bodies and neuritic processes of SNs cultured alone or with synaptic targets. Som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(98 citation statements)
references
References 45 publications
4
94
0
Order By: Relevance
“…PKC and rapamycin regulate the local synthesis of sensorin after tetanus plus 5-HT A single pairing produced a rapid increase in sensorin translation from sensorin mRNA that is located in the cell body, axons, and the distal varicosities (Schacher et al, 1999;Hu et al, 2002;Lyles et al, 2006). Tetanus plus 5-HT, however, modestly increased sensorin in the cell body of the sensory neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PKC and rapamycin regulate the local synthesis of sensorin after tetanus plus 5-HT A single pairing produced a rapid increase in sensorin translation from sensorin mRNA that is located in the cell body, axons, and the distal varicosities (Schacher et al, 1999;Hu et al, 2002;Lyles et al, 2006). Tetanus plus 5-HT, however, modestly increased sensorin in the cell body of the sensory neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid and significant increase in sensorin at distal varicosities by 0.5 h after stimulation suggested that local translation of sensorin mRNA, which accumulates at varicosities after being transported down sensory neuron axons (Schacher et al, 1999;Hu et al, 2002Hu et al, , 2006Lyles et al, 2006), contributes to local changes in sensorin levels. Local synthesis of sensorin is detected after removing the sensory neuron cell body; five applications of 5-HT produced a rapid rapamycin-sensitive and PI3K-dependent increase in sensorin synthesis in both the axons and varicosities (Hu et al, 2006).…”
Section: Sensory Neuron Cell Body Is Not Required For the Rapid Synthmentioning
confidence: 99%
“…Sensory neurons were isolated from pleural ganglia dissected from adult animals (80 -100 gm); motor cell L7 and L11 were isolated from juvenile (1-3 gm) abdominal ganglia and maintained in culture medium (2 ml) from 1 to 7 d as described previously (Rayport and Schacher, 1986;Schacher et al, 1999). Culture medium was a 1:1 (by volume) mixture of Aplysia hemolymph and L15 medium with added salts to match ionic composition of seawater (Rayport and Schacher, 1986).…”
Section: Methodsmentioning
confidence: 99%
“…In culture, Aplysia neurons (sensory neurons or interneuron L10) form specific synapses when confronted with either individual targets or multiple targets simultaneously (Camardo et al, 1983;Hawver and Schacher, 1993;Schacher et al, 1999). Many important cellular changes in sensory neurons accompany contact and synapse formation with motor neuron L7 compared with contact with motor neuron L11, which fails to form synapses with sensory neurons: an increase in presynaptic axon growth and varicosity formation contacting the target (Glanzman et al, 1989;Schacher and Montarolo, 1991), the full development of transmitter release sites in varicosities contacting L7 (Glanzman et al, 1989;Hatada et al, 1999, Kim et al, 2003, and differences in the expression and distribution of specific mRNAs that encode proteins critical for synaptic function Hu et al, 2002Hu et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation